Inhibiting PNP for the therapy of hyperuricemia in Lesch–Nyhan disease: Preliminary in vitro studies with analogues of immucillin‐G. Issue 1 (11th February 2019) - Jacomelli, Gabriella; Baldini, Eva; Mugnaini, Claudia; Micheli, Vanna; Bernardini, Giulia; Santucci, Annalisa
Abstract: Lesch‐Nyhan disease (LND) is a rare X‐linked genetic disorder, with complete hypoxanthine‐guanine phosphoribosyltransferase (HGPRT) deficiency, uric acid (UA), hypoxanthine and xanthine accumulation, and a devastating neurologic syndrome. UA excess, causing renal failure, is commonly decreased by xanthine oxidoreductase (XOR) inhibitors, such as allopurinol, yielding a xanthine and hypoxanthine increase. Xanthine accumulation may result in renal stones, while hypoxanthine excess seems involved in the neurological disorder. Inhibition of purine nucleoside phosphorylase (PNP) represents a different strategy for lowering urate. PNP catalyzes the cleavage of purine ribo‐ and d‐ribo‐nucleosides into ribose/deoxyribose phosphate and free bases, starting catabolism to uric acid. Clinical trials demonstrated that PNP inhibitors, initially developed as anticancer drugs, lowered UA in some gouty patients, in association or not with allopurinol. The present study tested the reliability of an analogue of immucillin‐G (C1a), a PNP inhibitor, as a therapy for urate, hypoxanthine, and xanthine excess in LND patients by blocking hypoxanthine production upstream. The therapeutic aim is to limit the administration of XOR inhibitors to LND patients by supplying the PNP inhibitor in low doses, avoiding d‐nucleoside toxicity. We report studies conducted in primary cultures of skin fibroblasts from controls and LND patients grown in the presence of the PNP inhibitor. Cell viability, oxypurine release in culture medium, and endocellular nucleotide pattern have been monitored in different growth conditions (inhibitor concentration, time, added inosine). Our results demonstrate effective PNP inhibition by low inhibitor concentration, with reduced hypoxanthine release, and no appreciable toxicity in control or patient cells, suggesting a new therapeutic strategy for LND hyperuricemia.